Application of homotopy perturbation sumudu transform method for solving heat and wave-like equations - Singh, Jagdev; Kumar, Devendra; Kilicman, Adem (Universiti Putra Malaysia Press, 2013)
In this paper, we use the homotopy perturbation sumudu transform method (HPSTM) to solve heat and wave-like equations. The proposed scheme finds the solution without any discretization or restrictive assumptions and avoids the round-off errors. Several examples are given to verify the reliability and efficiency of the method. The fact that the proposed technique solves nonlinear problems without using Adomian's polynomials can be considered as a clear advantage of this algorithm over the decomposition method.